THE USE OF PINE FRUIT WASTE AN ALTERNATIVE ENERGY SOURCE BASED ON GRANULE VARIATION - Sallolo Suluh, Martina Pineng, Suri Toding Lembang, Normalia Sirande, Silka & Chendri Johan (International Journal of Research Science and Management, 2017)
The use of Pine Fruit Waste as Alternative Energy Source in the form of charcoal briquettes was motivated by the great availability of pine fruits in North Toraja which is not utilized properly, only left as useless garbage. This study aims (1) to determine the calorific value of pine fruit charcoal briquettes in terms of granular variation (2) to determine the value of thermal efficiency in pine fruit charcoal briquettes in terms of grain variations. The used research method was experimental method by using pine waste as fuel for stove to boil water.The results of calorific test results obtained that briquette 1 was 5721 cal/gr, briquette 2 of 5340 cal/gr and briquette 3 of 5686 cal/gr. Burning test results showed that briquette 3 is the most superior in terms of boiling water as much as 3 (three) times and the burning efficiency of 43.58% followed by briquette 2 of 33.18% and briquette 1 of 32.17%.